Oleoylethanolamide, Neuroinflammation, and Alcohol Abuse - Orio, Laura; Alen, Francisco; Pavón, Francisco Javier; Serrano, Antonia; García-Bueno, Borja (Frontiers in Molecular Neuroscience, 2019)
Neuroinflammation is a complex process involved in the physiophatology of many central nervous system diseases, including addiction. Alcohol abuse is characterized by induction of peripheral inflammation and neuroinflammation, which hallmark is the activation of innate immunity toll-like receptors 4 (TLR4). In the last years, lipid transmitters have generated attention as modulators of parts of the addictive process. Specifically, the bioactive lipid oleoylethanolamide (OEA), which is an endogenous acylethanolamide, has shown a beneficial profile for alcohol abuse. Preclinical studies have shown that OEA is a potent anti-inflammatory and antioxidant compound that exerts neuroprotective effects in alcohol abuse. Exogenous administration of OEA blocks the alcohol-induced TLR4-mediated pro-inflammatory cascade, reducing the release of proinflammatory cytokines and chemokines, oxidative and nitrosative stress and, ultimately, preventing the neural damage in frontal cortex of rodents. The mechanisms of action of OEA are discussed in this review, including a protective action in the intestinal barrier. Additionally, OEA blocks cue-induced reinstatement of alcohol-seeking behavior and reduces the severity of withdrawal symptoms in animals, together with the modulation of alcohol-induced depression-like behavior and other negative motivational states associated with the abstinence, such as the anhedonia. Finally, exposure to alcohol induces OEA release in blood and brain of rodents. Clinical evidences will be highlighted, including the OEA release and the correlation of plasma OEA levels with TLR4-dependent peripheral inflammatory markers in alcohol abusers. In base of these evidences we hypothesize that the endogenous release of OEA could be a homeostatic signal to counteract the toxic action of alcohol and we propose the exploration of OEA-based pharmacotherapies to treat alcohol use disorders.